Peptide–Oleate Complexes Create Novel Membrane-Bound Compartments. (10th June 2020) - Hansen, Jesper S; Tran, Tuan Hiep; Cavalera, Michele; Paul, Sanchari; Chaudhuri, Arunima; Lindkvist-Petersson, Karin; Ho, James C S; Svanborg, Catharina
Abstract: A challenging question in evolutionary theory is the origin of cell division and plausible molecular mechanisms involved. Here, we made the surprising observation that complexes formed by short alpha-helical peptides and oleic acid can create multiple membrane-enclosed spaces from a single lipid vesicle. The findings suggest that such complexes may contain the molecular information necessary to initiate and sustain this process. Based on these observations, we propose a new molecular model to understand protocell division.